PENGARUH PENGGUNAAN SISTEM ISYARAT BAHASA DAN DEMONSTRASI TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM PADA SISWA TUNA RUNGU KELAS 5 DI SLB PANCA BAKTI MAGETAN DAN SLB PGRI KAWEDANAN MAGETAN - Sucipto, Sucipto (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Inhibition of the sense of hearing makes deaf children can not understand the language. Deaf children need to use a medium or tool that understandable to children so that they can assist learning in school. These limitations led to obstacles in their education, so it is necessary to appropriate learning media in order to make them can achieve maximum learning results. The study was a non-experimental study involving 45 students as much as students study sample, wherein the sample is obtained by purposive sampling. data analysis technique is to multiple linear regression analysis. The results of the study obtained are:Â  1) The use of cue language system affects language Natural Science learning result in deaf students of 5th grade in SLB Panca Bakti Magetan and SLB PGRI Kawedanan Magetan indicated by the count r positive and strong, with the count value of r = 0.676. Moreover t is greater then t table, namely (4.890> 2.021); 2) The use of the demosntration method affect on the Natural Sciences learning result on deaf students in grade 5 SLB Panca Bakti Magetan and SLB PGRI Kawedanan Magetan indicated by the value of r is calculated, ie 0.513. Moreover indicated by t value is greater than t table, namely (2.573> 2.021); and 3) use of language cue systems and demonstration methods effect on the learning result on the Natural Sciences at the deaf studentsÂ  of 5th grade in SLB Panca Bakti Magetan and SLB PGRI Kawedanan Magetan, as indicated by the robust count value of r, ie 0.728. Additionally count indicated by the larger F table, ie (23.714> 3.25)Key Words: Language Cue system, demonstration method, learning result, deaf students